China - From Poor Areas to Poor People : China's Evolving Poverty Reduction Agenda - An Assessment of Poverty and Inequality in China : Executive Summary - World Bank (World Bank, 2012)
China's progress in poverty reduction over the last 25 years is enviable. One cannot fail to be impressed by what this vast nation of 1.3 billion people has achieved in so little time. In terms of a wide range of indicators, the progress has been remarkable. Poverty in terms of income and consumption has been dramatically reduced. Progress has also been substantial in terms of human development indicators. Most of the millennium development goals have either already been achieved or the country is well on the way to achieving them. As a result of this progress, the country is now at a very different stage of development than it was at the dawn of the economic reforms at the beginning of the 1980s. China's poverty reduction performance has been even more striking. Between 1981 and 2004, the fraction of the population consuming below this poverty line fell from 65 percent to 10 percent, and the absolute number of poor fell from 652 million to 135 million, a decline of over half a billion people. The most rapid declines in poverty, in both the poverty rate and the number of poor, occurred during the 6th, 8th, and 10th plans. During the 7th plan period the number of poor actually rose, while in the 9th plan period, the poverty rate declined only marginally. But the pace of poverty reduction resumed between 2001 and 2004 and there are indications that during the first couple of years of the 11th plan poverty has continued to decline rapidly. The most recent official estimate of rural poverty in China for 2007 puts the number of poor at 14.79 million, or less than 2 percent of the rural population. While there is no official urban poverty line, estimates by others have found poverty levels in urban areas to be negligible using an urban poverty line that is comparable to the official poverty line for rural areas. These estimates thus suggest that only about 1 percent of China's population is currently in extreme poverty. Notwithstanding this tremendous success, the central thesis of this report is that the task of poverty reduction in many ways continues and in some respects has become more demanding.